2003
DOI: 10.1097/01.ss.0000080332.10341.ed
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Myo-Inositol Hexakisphosphate in Alkaline Soil Extracts by Solution 31p NMR Spectroscopy and Spectral Deconvolution

Abstract: Inositol phosphates are the dominant class of organic phosphorus (P) compounds in most soils, but they are poorly understood because they are not easily identified in soil extracts. This study reports a relatively simple technique using solution 31P NMR spectroscopy and spectral deconvolution for the quantification of myo-inositol hexakisphosphate (phytic acid), the most abundant soil inositol phosphate, in alkaline soil extracts. An authentic myo-inositol hexakisphosphate standard added to a re-dissolved soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 33 publications
6
93
0
2
Order By: Relevance
“…In acidic soils, associations with amorphous Al and Fe hydroxides are believed to be the most important mechanism of IP 6 stabilization (Celi and Barberis, 2007). This is supported by correlations between amorphous metals and IP 6 across a wide variety of soils (Anderson et al, 1974;McKercher and Anderson, 1968;Turner et al, 2007Turner et al, , 2003Vincent et al, 2012). However, the relative contribution of these stabilization processes remains poorly understood, in part because most recent studies have extracted IP 6 from soils by a single-step NaOH-EDTA procedure, which is assumed to extract mineral associated IP 6 as well as IP 6 associated with the organic soil matrix (Turner et al, 2005a).…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…In acidic soils, associations with amorphous Al and Fe hydroxides are believed to be the most important mechanism of IP 6 stabilization (Celi and Barberis, 2007). This is supported by correlations between amorphous metals and IP 6 across a wide variety of soils (Anderson et al, 1974;McKercher and Anderson, 1968;Turner et al, 2007Turner et al, , 2003Vincent et al, 2012). However, the relative contribution of these stabilization processes remains poorly understood, in part because most recent studies have extracted IP 6 from soils by a single-step NaOH-EDTA procedure, which is assumed to extract mineral associated IP 6 as well as IP 6 associated with the organic soil matrix (Turner et al, 2005a).…”
Section: Introductionmentioning
confidence: 51%
“…Several studies have reported correlations between IP 6 and amorphous metal oxides in acidic soils (Anderson et al, 1974;Giaveno et al, 2008;McKercher and Anderson, 1968;Turner et al, 2003). In addition, IP 6 concentrations have been shown to fluctuate in parallel with changes in amorphous Al and Fe hydroxides during long-term pedogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra are plotted with 1 Hz line broadening. (Turner et al, 2003b). ‡ Determined by integration of the signal at 4.2 ppm (Turner and Richardson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Spectra were plotted with a line broadening of 1 Hz to preserve resolution in the phosphate monoester region. Concentrations of myo-inositol hexakisphosphate were determined by multiplying by six the signal at approximately 5.9 ppm arising from the C-2 phosphate on the inositol ring (Turner et al, 2003b). Quantification of the three other signals from this compound tends to overestimate myo-inositol hexakisphosphate due to interference with signals from other compounds.…”
Section: Analytical Proceduresmentioning
confidence: 99%